Um estudo sobre o ensino da arte: proposta curricular de Santa Catarina e a prática docente - Maciel, Silésia de Aguiar Mendes (2007)
This study focuses on art language, theoretical assumptions for teaching, and investigation of teaching practices in primary school, offering suggestions for such practice. Considerations upon art and its introduction in the Brazilian educational system are made. Theoretical assumptions for teaching art according to the guidelines recommended by the 1998 Santa Catarina curriculum proposal are also evoked. Field research data analysis is carried out following the theoretical guidelines presented here. Ten teachers from five downtown Criciúma state schools and five from the outskirts of the city were engaged in the research to investigate how art is being taught in the different classes. The current study aims at contributing for the elaboration of a document designed to help teachers think about art and teach their students following the established principles. The relevance of the 1998 Santa Catarina curriculum proposal in stimulating art teachers‟ awareness of their important role in shaping citizens is also highlighted. The main objective of this study is to identify art language features and teachers‟ comprehension of the Santa Catarina curriculum proposal in their daily practice, such as bringing art work from local artists to school as recommended. In conclusion, the importance of an educational policy for teaching art is established. Another conclusion is that exercises of imagination, self-expression, discovery and creation recover one of the teaching functions, that is, to create a new space for perceptive experiences provided by the diversity of values, senses and intentions. The 1998 Santa Catarina curriculum proposal can also be better studied and applied.